2007
DOI: 10.3168/jds.2006-613
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal and Intestinal Degradability of Distillers Grains plus Solubles Varies by Source

Abstract: Currently in the dairy industry, there is a concern about the variability in the nutrient content among sources of distillers grains plus solubles (DG), but little research has evaluated the variability in metabolizable AA among sources. The ruminal degradability of crude protein (CP) in soybean meal (SBM), dried DG from 5 sources (DG1, DG2, DG3, DG4, and DG5), and 1 source of wet DG (WDG) were determined using 2 lactating ruminally cannulated Holstein cows. Feeds were incubated in the rumen for 3, 6, 12, 18, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
102
11

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(134 citation statements)
references
References 24 publications
21
102
11
Order By: Relevance
“…The protein fractions reported for the co-products in this study are comparable to values determined by Kleinschmit et al (2007) on 5 DDGS produced at various ethanol plants. In their study, values ranged from 5.2 to 9.8, 0.1 to 1.8, 40.9 to 51.1, 22.7 to 41.4, and 7.5 to 23.1% CP for fractions A, B 1 , B 2 , B 3 , and C, respectively.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The protein fractions reported for the co-products in this study are comparable to values determined by Kleinschmit et al (2007) on 5 DDGS produced at various ethanol plants. In their study, values ranged from 5.2 to 9.8, 0.1 to 1.8, 40.9 to 51.1, 22.7 to 41.4, and 7.5 to 23.1% CP for fractions A, B 1 , B 2 , B 3 , and C, respectively.…”
Section: Discussionsupporting
confidence: 71%
“…The only co-product that was higher in RUP than HPDDG was DDGS2, which may be due to heat-damaged protein as indicated by its low soluble protein content (16.6% of CP), high ADIN content (25.0% of CP), and corresponding high protein fraction C (27.9% of CP). In addition, co-products with higher C fractions also had correspondingly elevated ADF contents likely caused by excessive heating (Kleinschmit et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, the DM ruminal digestibility using passage rates (kp) of CPM Dairy ) cows indicated that GERM would have the greatest ruminal degradability; BRAN and BPX would have similar values, but HP-DDG would be the corn milling (co)product with the lowest ruminal degradability (Table 2). Kleinschmit et al (2007) evaluated ruminal degradation and intestinal digestion of DDGS and reported differences in RUP among 5 different sources of DDGS. As shown in Table 2, CPM Dairy simulations predicted that the DM ruminal degradation varied from 78.1 to 82.3% for dry cows (kp = 0.04 h ), and 64.3 to 70.1% (kp = 0.08 h −1 ) for high-producing lactating cows based on the fractional rate of fermentation of the intact feed.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the AA composition of UDP and its intestinal digestibility (ID) are further important characteristics of the protein value of a feedstuff (Weisbjerg et al, 1996). Unlike the well-balanced AA profile supplied by the microbial protein, AAs coming from the UDP largely reflect the AA pattern of the original feed (Kleinschmit et al, 2007;Mjoun et al, 2010;Li et al, 2012). However, AAs of the UDP sometimes do not match the AA needs of the cow in terms of concentration and digestibility.…”
Section: Introductionmentioning
confidence: 99%
“…This may become especially relevant if the UDP content of a feedstuff is high and one AA is particularly low, as is the case for lysine in DDGS. Knowledge about whether or not the AA composition of DDGS and UDP fraction of DDGS are similar is important for ration formulation and has been reported so far (Kleinschmit et al, 2007;Mjoun et al, 2010;Li et al, 2012). However, these experiments only considered a maximum of five samples of DDGS mainly originating from corn and did not consider blend-DDGS or DDGS originating from a wide variety of grains or mixtures like those produced under European conditions.…”
Section: Introductionmentioning
confidence: 99%